The role of entrepreneurship in enhancing economic development: the mediating role of gender and motivations - Rusu, Valentina Diana; Roman, Angela; Boghean, Carmen; Boghean, Florin (Journal of Business Economics and Management, 2025)
Starting from the significant role played by entrepreneurship in the economy and also from the pressing problem of gender inequality, in this paper we aim to analyse the link between entrepreneurship and economic development, with emphasis on the mediating role of gender and motivations of entrepreneurs. We apply panel data regression models on a sample of 53 world countries mapped by their development level. Data regarding countries’ economic development levels is obtained from the World Bank DataBank and the entrepreneurship rates from the annual reports of the Global Entrepreneurship Monitor. The level of economic development is measured by GDP per capita. Entrepreneurship rates by gender and motivations are used to test the mediating role. The results emphasise that male entrepreneurs motivated by necessity and female entrepreneurs motivated by opportunity would significantly stimulate economic development. The analysis of clusters of countries highlights that entrepreneurship enhances economic development, but the effects broken down by gender and motivations have particularities depending on the country. This study contributes to the literature in several ways, such as the comparative analysis, its large sample size and the emphasis on gender differences and entrepreneurs’ motivations.